Evaluación del rendimiento del cultivo de uvilla (Physalis peruviana L.) bajo dos sistemas de producción, sometido a la aplicación de abonos orgánicos y N-P-K, en el Sector Miraflores, Provincia del Carchi - Romo Ruiz, Javier Rolando (2018)
VII. SUMMARY The present investigation was carried out in Miraflores Sector, Province of Carchi, located at an altitude of 2.850 meters above sea level, focused on determining the yield of uvilla (Physalis peruviana L.) under greenhouse and open field, subjected to the application of humus of worm and / or bovine in doses of 4 kg and 6 kg at the time of transplant and NPK in doses of 300 g and 400 g of 12-36-16 at 30 and 90 days after sowing, for each experimental unit, in addition to two control treatments. An experimental design of Complete Randomized Blocks (DBCA) was used, with a factorial arrangement (A x B + 2), with ten treatments and three repetitions. The variables evaluated were: Percentage of yield, height of plant, days to flowering, days to harvest, number of fruits, weight of fruits and yield per hectare. The percentage of average seizure achieved at 15 days after transplantation was 99.70%. The grape harvest under greenhouse began at 163 days; while in the open field at 176 days. The fertilization with 4 kg earthworm humus + 300 g NPK under greenhouse reached the highest yield of uvilla per hectare with 24,480 Kg / ha, showing significant statistical differences with the performance of the control treatments in the open field and control under greenhouse with 14,206 , 67 Kg / ha and 19,473.33 Kg / ha, respectively.